The Financial Power of the Powerless: Socio‐Economic Status and Interest Rates Under Partial Rule of Law. (30th April 2017) - Kuran, Timur; Rubin, Jared
Abstract: In advanced economies interest rates vary inversely with the risk of default, which itself is negatively related to the borrower's socio‐economic status. The former relationship depends on the impartiality of the law. Where the law is markedly biased in favour of certain groups, these groups will pay a surcharge for capital. Legal power, as measured by privileges before the law, thus undermines financial power, the capacity to borrow cheaply. Developing this argument, this article also tests it through judicial records from Ottoman Istanbul, 1602–1799. Three privileged Ottoman groups–men, Muslims and titled elites–all paid relatively high interest rates conditional on various loan characteristics.